Cultural revolutions reduce complexity in the songs of humpback whales - Allen, Jenny A.; Garland, Ellen C.; Dunlop, Rebecca A.; Noad, Michael J. (Proceedings of the Royal Society B: Biological Sciences, 2018)
J.A.A. was funded by an Australian Government Research Training Programme Scholarship and the Australian American Association University of Queensland Fellowship. E.C.G. was funded by a Royal Society Newton International Fellowship and a Royal Society University Research Fellowship. The HARC project was funded by the US Office of Naval Research, the Australian Defence Science and Technology Organisation and the Australian Marine Mammal Centre. The BRAHSS project was funded by the E&P Sound and Marine Life Joint Industry Programme and the US Bureau of Ocean Energy Management. Much evidence for non-human culture comes from vocally learned displays, such as the vocal dialects and song displays of birds and cetaceans. While many oscine birds use song complexity to assess male fitness, the role of complexity in humpback whale (Megaptera novaeangliae) song is uncertain owing to population-wide conformity to one song pattern. Although songs change gradually each year, the eastern Australian population also completely replaces their song every few years in cultural 'revolutions'. Revolutions involve learning large amounts of novel material introduced from the Western Australian population. We examined two measures of song structure, complexity and entropy, in the eastern Australian population over 13 consecutive years. These measures aimed to identify the role of complexity and information content in the vocal learning processes of humpback whales. Complexity was quantified at two hierarchical levels: the entire sequence of individual sound 'units' and the stereotyped arrangements of units which comprise a 'theme'. Complexity increased as songs evolved over time but decreased when revolutions occurred. No correlation between complexity and entropy estimates suggests that changes to complexity may represent embellishment to the song which could allow males to stand out amidst population-wide conformity. The consistent reduction in complexity during song revolutions suggests a potential limit to the social learning ...